Hybrid Intelligent Systems 17th International Conference on Hybrid Intelligent Systems (HIS 2017) held in Delhi, India, December 14-16, 2017 - Abraham, Ajith; Muhuri, Pranab Kr; Muda, Azah Kamilah; Gandhi, Niketa (Advances in Intelligent Systems and Computing, 2018)
This book includes recent research on Hybrid Intelligent Systems. It presents 35 selected papers from the 17th edition of the International Conference on Hybrid Intelligent Systems (HIS), which was held in Delhi, India from December 14 to 16, 2017. Reflecting the awareness in the respective academic communities that combined approaches are essential to solving the remaining tough problems in computational intelligence, the HIS is a premier conference focused on the hybridization of intelligent systems. The book offers a valuable reference guide for all researchers, students and practitioners in the fields of Computer Science and Engineering.